2022
DOI: 10.23917/indigenous.v7i3.18838
|View full text |Cite
|
Sign up to set email alerts
|

Assertive Student Victims of Domestic Violence: Basic Qualitative Analysis From Guidance and Counseling Perspective

Abstract: Abstract. Domestic Violence is mostly experienced by women and children. Victims of domestic violence will be moody, quiet, aggressive, and tend to have less assertive behavior. Assertive behavior is the ability to convey what you want, feel, and think to others openly and honestly without intending to offend. This study aims to determine the description of assertive behavior in child victims of domestic violence. The study was conducted on 4 student victims of domestic violence (4 girls; aged 17-19 years; stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Few studies reported similar findings which revealed that silence helps them to know what situations and circumstances to avoid. [ 45 ] employing a problem-focused approach, [ 46 ] engaging in assertive communication, [ 47 ] preparing safety plans, [ 48 ] striving for financial independence, [ 49 ] utilizing emotional-focused techniques, [ 31 ] relying on religious/spiritual strategies, [ 50 ] practising relaxation techniques, [ 51 ] employing social coping mechanisms, [ 7 ] seeking assistance from others, [ 52 ] supporting the husband’s treatment, and accessing peer support groups. [ 53 ]…”
Section: Discussionmentioning
confidence: 99%
“…Few studies reported similar findings which revealed that silence helps them to know what situations and circumstances to avoid. [ 45 ] employing a problem-focused approach, [ 46 ] engaging in assertive communication, [ 47 ] preparing safety plans, [ 48 ] striving for financial independence, [ 49 ] utilizing emotional-focused techniques, [ 31 ] relying on religious/spiritual strategies, [ 50 ] practising relaxation techniques, [ 51 ] employing social coping mechanisms, [ 7 ] seeking assistance from others, [ 52 ] supporting the husband’s treatment, and accessing peer support groups. [ 53 ]…”
Section: Discussionmentioning
confidence: 99%